Combining iterative analytical reasoning and software development using the visualization language Processing - Muller-Birn, C.; Birn, L. (2009 IEEE Symposium on Visual Analytics Science and Technology, 2009)
Processing is a very powerful visualization language which combines software concepts with principles of visual form and interaction. Artists, designers and architects use it but it is also a very effective programming language in the area of visual analytics. In the following contribution Processing is utilized in order to visually analyze data provided by IEEE VAST 2009 Mini Challenge Badge and Network Traffic. The applied process is iterative and each stage of the analytical reasoning process is accompanied by customized software development. The visual model, the process and the technical solution will be briefly introduced.